Behavioral Reasons for New Product Failure: Does Overconfidence Induce Overforecasts?1. Issue 5 (24th November 2014) - Markovitch, Dmitri G.; Steckel, Joel H.; Michaut, Anne; Philip, Deepu; Tracy, William M.
<x xml:space="preserve">Abstract</x> Efforts to organize and integrate research findings on new product performance determinants have lagged since the last significant overview paper appeared over a decade ago. Importantly, this literature has not considered entire categories of factors that are known to affect managerial decisions and behavior, namely those that pertain to decision‐makers' cognitive limitations and incentive structures. This research empirically investigates one specific cognitive distortion heretofore neglected in studies of new product commercialization—overconfidence, commonly defined in the literature as excessive belief in one's own abilities to generate superior performance. To lay the groundwork for subsequent exploration, the paper first introduces a behavioral model that both organizes well‐understood new product performance determinants and illuminates others heretofore not studied, namely incentive alignment and cognitive limitations and biases. The model summarizes extant research and allows development of research hypotheses related to overconfidence. The hypotheses and empirical investigation motivated by the model address two questions about the impact of overconfidence on new product commercialization activities. First, the study explores whether overconfidence is associated with overforecasting new product demand. Second, it evaluates two complementary mechanisms that may account for overconfidence‐induced overforecasts. The empirical findings are based on data generated in the course of management simulation workshops conducted among graduate students at three leading business schools in India. Three hundred thirty participants played individually four rounds of a computer‐based simulation game that involved decisions pertaining to new product development (including product formulation) and commercialization strategies. The decisions were captured and analyzed using statistical techniques. The results reveal that decision‐makers' overconfidence is associated with a higher likelihood of overforecasting new product sales. The observed effect is fully mediated by flawed tactical decisions that dampen demand, namely elevated product pricing. Sensitivity analyses show that these results are robust to a number of alternative explanations. However, the study finds no evidence implicating overconfident individuals as poor "innovators"—overconfident and nonoverconfident decision‐makers experienced comparable market demand for their new products. The paper concludes with a discussion of the results and provides specific recommendations for practice.